TINJAUAN HUKUM DIPLOMATIK TENTANG PENYELESAIAN SENGKETA PRAKTIK SPIONASE YANG DILAKUKAN MELALUI MISI DIPLOMATIK DILUAR PENGGUNAAN PERSONA NON-GRATA - I Gst Ngr Hady Purnama Putera; Ida Bagus Putu Sutama (Kertha Negara : Journal Ilmu Hukum, 2013)
The practice of spying or espionage, has long been a problem in the dysfunctionof Diplomatic and Consular Relations and also Diplomatic immunity inherent withinthe Diplomatic and Consular itself. Indeed, International Law has provided a Personanon-Grata mechanism for the receiving State, but, in many cases, this principle has animpact on the relations between the two States, in fact it is not uncommon to be atension. This paper will discuss a lot about a result of the misuse of diplomatic missionsthat become the practice of espionage, and how the dispute settlement beside using thePersona non-Grata principle.